Charcot - Marie - Toots disease: description of 2 clinical cases of the disease in members of the same family (father and daughter) - V. S. Fedorova; A. G. Smochilin; A. I. Kulyakhtin; A. A. Yakovlev; M. S. Pushkaryov; A. V. Gavrichenko; E. A. Gavrilova; R. A. Gapeshin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Charcot — Marie — Tooth disease belongs to a genetically heterogeneous group of monogenic diseases with a predominant lesion of the peripheral nervous system associated with predominant degeneration of the myelin sheath and/or axon of the motor and sensory nerves and spinal roots, accompanied by motor disorders and specific pain syndrome. The article presents a description of 2 clinical cases of patients (father and daughter), whose disease was manifested by chronically progressive weakness and atrophy of the distal limb muscles, reflexes reduction, foot and hand deformation, gait changes and sensory disorders. Genetic tests were performed to detect duplication/deletion of the PMP22 gene and the expansion of GAA repeats in the FXN gene, which yielded negative results. Based on complaints, neurological examination, family medical history and data of instrumental research (EMNG), we made a clinical diagnosis of the CMT with an autosomal dominant type of inheritance and a high degree of penetrance. At the department, patients received the infusion therapy (neurometabolic therapy, vitamin therapy), physical therapy courses according to an individual plan, physiotherapy and reflexotherapy with a moderate positive effect in the form of a subjective increase in muscle strength in the lower extremities, increasing walking stability and confidence. The article also highlights the peculiarities of the pathogenesis of different genetic variants of CMT and prospect for pathogenetic treatment of this disease.